2017
DOI: 10.1007/s11325-017-1490-9
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the right interface for positive airway pressure therapy in patients with obstructive sleep apnea

Abstract: Current evidence suggests that the nasal mask is better tolerated, requires lower pressure to eliminate obstructive respiratory events, and is associated with a better sleep quality and better PAP therapy compliance. Nevertheless, the best mask is the one that patient will wear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The development of nasal side effects with CPAP treatment may be related to the induction of this type of inflammatory response. However, in another study, it was shown that inflammatory markers in sputum of OSA patients before and after use of CPAP for a month remained unchanged and an increase in airway hyperresponsiveness was observed . In other work, application of 10 cm H 2 O n‐CPAP for 5 h caused a threefold increase in the number of neutrophils found in the nasal mucosa .…”
Section: Pressure‐related Side Effectsmentioning
confidence: 89%
“…The development of nasal side effects with CPAP treatment may be related to the induction of this type of inflammatory response. However, in another study, it was shown that inflammatory markers in sputum of OSA patients before and after use of CPAP for a month remained unchanged and an increase in airway hyperresponsiveness was observed . In other work, application of 10 cm H 2 O n‐CPAP for 5 h caused a threefold increase in the number of neutrophils found in the nasal mucosa .…”
Section: Pressure‐related Side Effectsmentioning
confidence: 89%
“…Therefore, in this context, it is important to understand the physiological effects of positive airway pressure applied through different interfaces on upper airway dynamics. 6,36 To understand the effects of different interfaces on upper airway patency, we need to briefly review the difference between nose breathing and mouth breathing. 37 When breathing occurs through the mouth, there is an increase in upper airway resistance and an increased tendency to develop upper airway obstruction.…”
Section: Interface Type and Upper Airway Obstructionmentioning
confidence: 99%
“…For interface choice in patients with stable sleep-disordered breathing, readers are referred to a recently published review. 6…”
mentioning
confidence: 99%
“…Oronasal breathing may adversely impact OSA patients either by increasing upper airway collapsibility or by influencing continuous positive airway pressure (CPAP) treatment outcomes (1). Self-reported oronasal breathing is a common reason for oronasal CPAP prescription (3,20,27). However, oronasal CPAP has been linked to poorer outcomes compared with nasal CPAP (4,9).…”
Section: Introductionmentioning
confidence: 99%
“…Although oronasal CPAP is associated with poorer adherence, a higher residual apnea-hypopnea index (AHI), and higher therapeutic levels than nasal CPAP, 25-50% of CPAP prescriptions are for oronasal CPAP (4, 5a, 7-9). Self-reported oronasal breathing and nasal symptoms often influence the choice of oronasal masks for CPAP treatment of OSA patients (3,27). Self-reported nasal obstruction has been shown to be poorly associated with objective measures of nasal patency (19,28).…”
Section: Introductionmentioning
confidence: 99%